2011
DOI: 10.1145/2063239.2063243
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do Search Engines Support Code Retrieval on the Web?

Abstract: Software developers search the Web for various kinds of source code for diverse reasons. In a previous study, we found that searches varied along two dimensions: the size of the search target (e.g., block, subsystem, or system) and the motivation for the search (e.g., reference example or as-is reuse). Would each of these kinds of searches require different search technologies? To answer this question, we conducted an experiment with 36 participants to evaluate three diverse approaches (general purpose informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
66
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 57 publications
(42 reference statements)
6
66
0
4
Order By: Relevance
“…We stopped mining a little over 10M classes because of a noticeable delay in processing queries on our servers (unacceptable when users expect queries to be processed in a few seconds). However, we also thought 10M classes allowed us to closely approximate an Internet scale code search engine when compared against the sizes of the Internet code search engines Koders (600K), Krugle (3.5M), and Google Code Search (2.5M) [108].…”
Section: Instantiating the Index For Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We stopped mining a little over 10M classes because of a noticeable delay in processing queries on our servers (unacceptable when users expect queries to be processed in a few seconds). However, we also thought 10M classes allowed us to closely approximate an Internet scale code search engine when compared against the sizes of the Internet code search engines Koders (600K), Krugle (3.5M), and Google Code Search (2.5M) [108].…”
Section: Instantiating the Index For Experimentsmentioning
confidence: 99%
“…Given the advantages and disadvantages of search engines today and the importance of search in developing software (programmers report searching for code frequently as part of their practice [97], [108]), software engineering researchers are investigating how to improve code search engines. Some, for instance, have been investigating how to support more expressive queries (e.g., searching by test case or method signatures) that afford more precise matching of code compared to keywords (e.g., [4], [15], [54], [65], [71], [82], [91], [110], [122], [142]).…”
mentioning
confidence: 99%
“…Recent studies have revealed that programmers typically use general search engines to find code for reuse [21]. More specialized code search engines (e.g., Koders, Krugle, ohloh) incorporate various filtering capabilities (e.g., language, domain, scores) and program syntax into the query to better guide the matching process [21]. Other approaches add natural language processing to increase the potential matches [8], [16].…”
Section: Related Workmentioning
confidence: 99%
“…INTRODUCTION Today, searching for code is a regular activity for most programmers [21]. Yet, the mechanisms to support this activity have barely evolved in the last decade, and the limitations are becoming more apparent as code repositories get richer and programmers' expertise and needs more diverse.…”
mentioning
confidence: 99%
See 1 more Smart Citation